Educational Interpretation Strategies in Answering Students' Psychosocial Challenges in the Era of Globalization - Masyhuri, Ahmad Ari; Yuspitasari, Selvy (Universitas Pahlawan Tuanku Tambusai, 2025)
The era of globalization has had a significant impact on the social, cultural and psychological lives of students. Rapid technological and information developments require students to be adaptable, but also give rise to various psychosocial challenges such as stress, anxiety, identity crises and social pressure. This article aims to examine educational interpretation strategies as an alternative approach to addressing these challenges. Educational interpretation approaches offer a holistic perspective by integrating religious, moral and spiritual values into educational practices. Through a qualitative literature-based study, this article identifies that educational interpretation strategies can provide new meaning to the learning process, focusing not only on cognition but also on character development and emotional balance in students. The study's findings indicate that education based on the values of Quranic interpretation, for example, can foster psychological resilience, social empathy and self-awareness in students facing the complex currents of globalization. Thus, educational interpretation strategies are a relevant and applicable solution to address the psychosocial challenges of today's students.